The Role of Cultural Memory in Achieving Psychosocial Well-being in Historic Urban Landscape Conservation - Hussein, Fatmaelzahraa (Curtin University, 2020)
This research aimed to study the role of cultural memory in achieving psychosocial well-being in Historical Urban Landscape (HUL) conservation. This was achieved by studying several case studies in Alexandria, Egypt. The study adopted the grounded theory qualitative approach. This PhD contributes towards understanding the intangible, psychosocial effect of cultural memory in realising well-being in historic landscapes. The output from this study can be used as a case model to improve future HUL conservation plans.